122. Quantitative performance evaluation of two linear accelerators through Low function. (December 2018) - Candiano, G.; Borzì, G.R.; Franza, N.
Abstract: Purpose: Department of REM Radioterapia and Fondazione IOM is equipped with two linear accelerators: TrueBeam Novalis STx and Trilogy by Varian (Palo Alto). In this work the performance of the two accelerators is analyzed in terms of Low function[1] expressed in tabular form and calculated on a homogeneous patient cohort. Methods: Analysis was performed by selecting patients treated with IMRT and VMAT techniques, for prostate, head and neck and mediastinum cancers. Pre-treatment verifications were carried out using the Delta4+ system by Scandidos (Uppsala), equipped with 1069 diodes (area 0.78 mm 2 distributed on two orthogonal planes mounted in a cylindrical phantom. To evaluate the Low function, Local Gamma 3%–3 mm criterion was used at prescription dose, including diodes in the dose range 20–500%, threshold of 95%. The Delta4+ software includes a new tabular display of Low function that shows the function behavior at varying dose and distance. For each plan, the Gamma Index matrices were calculated for Dose Difference (DD) in the range 0.5–5% and Distance to Agreement (DTA) in the range 0.5–5 mm. To evaluate possible differences between the two accelerators, Gamma Index values of treatments subdivided by pathology were compared, carrying out an arithmetic average on the matrices. Results: For prostate treatments, a Gamma Index value greater than 95% was obtained up to 2.5%-2.5 mm DD-DTA for TrueBeam Novalis STx accelerator and up to 3%-2.5 mm DD-DTA for Trilogy accelerator, as shown in the table below. Similar results were obtained for head and neck and mediastinum districts. Conclusion: The comparison between Gamma Index matrices of various anatomical districts showed the capability of this verification system to distinguish the different beam delivery of the two accelerators due to different multileaf collimators (minimum leaf size at isocenter of 2.5 mm for TrueBeam Novalis STx and 5 mm for Trilogy).